Lysosome-Dependent LXR and PPARδ Activation Upon Efferocytosis in Human Macrophages - Mota, Ana Carolina; Dominguez, Monica; Weigert, Andreas; Snodgrass, Ryan G.; Namgaladze, Dmitry; Brüne, Bernhard (Frontiers in Immunology, 2021)
Efferocytosis is critical for tissue homeostasis, as its deregulation is associated with several autoimmune pathologies. While engulfing apoptotic cells, phagocytes activate transcription factors, such as peroxisome proliferator-activated receptors (PPAR) or liver X receptors (LXR) that orchestrate metabolic, phagocytic, and inflammatory responses towards the ingested material. Coordination of these transcription factors in efferocytotic human macrophages is not fully understood. In this study, we evaluated the transcriptional profile of macrophages following the uptake of apoptotic Jurkat T cells using RNA-seq analysis. Results indicated upregulation of PPAR and LXR pathways but downregulation of sterol regulatory element-binding proteins (SREBP) target genes. Pharmacological inhibition and RNA interference pointed to LXR and PPARdelta as relevant transcriptional regulators, while PPARdelta did not substantially contribute to gene regulation. Mechanistically, lysosomal digestion and lysosomal acid lipase (LIPA) were required for PPAR and LXR activation, while PPARdelta activation also demanded an active lysosomal phospholipase A2 (PLA2G15). Pharmacological interference with LXR signaling attenuated ABCA1-dependent cholesterol efflux from efferocytotic macrophages, but suppression of inflammatory responses following efferocytosis occurred independently of LXR and PPARdelta. These data provide mechanistic details on LXR and PPARdelta activation in efferocytotic human macrophages.